The Use of Drone in Property Valuation - Ain Wahida Mohd Radzali, Nurul; Nizam Tahar, Khairul (International Journal of Engineering and Technology, 2018)
Unmanned Aerial Vehicles (UAV) photogrammetric image is an essential element in property information to calculate the rate of tax assessment on a double-storey housing scheme. The geometrical identification of double-storey terrace houses is very important for rate and tax assessments. Therefore, UAV photogrammetric image can be used to view and estimate the actual and real-view dimension of each double-storey house. The aim of this is to identify the actual geometry of each double-storey house based on the pattern of the roof between two houses. The method used to calculate the rate and tax is based on the current condition of the roof of each double-storey house which can represent the extension of the house. The new rate on the tax assessment can be calculated by referring to each parameter as mentioned in the local authorities guidelines. The assessment required the standard rate on the area, the period and the percent of extension. The results from this assessment were calculated into a year and half-year. For the extent condition, it was categorised into no extent, intermediate extent and extensive extent. UAV is very useful in rate and tax for property assessment because it can provide an aerial view and reliable results for property assessment.Â Â